The Effectiveness of Red Ginger Tamarind Tea (Kusamera Tea) on Reducing Menstrual Pain in Adolescent Girls - Barir, Baroroh; Fatmawati, Zeny; Aini, Inayatul; Kristianingrum, Dhita Yuniar (Jurnal MIDPRO, 2024)
Pain that occurs during menstruation that is common in adolescent adolescents due to an increase in prostaglandins (PG). F2-alpha which is a cyclooxygenase (COX-2) that results in hypertonus and vasoconstriction in the myometrium. The purpose of this study is to determine the effectiveness of the red ginger acid turmeric on reducing the intensity of menstrual pain. Type of Quantitative Research, The research design used is pre-experiment with one group pretest-postest design. The number of samples was 60 adolescent female respondents at ITKes Icme Jombang, who experienced menstrual pain. In this study, the sample was treated by consuming 200cc/day of sour turmeric during the 1st-3rd day of menstruation, and pain measurements were carried out before and after consuming red ginger tamarind turmeric. In sampling, the data analysis was carried out using the purposive sampling technique with the T-test. The results of the statistical test were obtained with a mean of 1. 268Sd 0. 058 p value 0.000 means that H0 is rejected and Ha is accepted, which means that there is an Effect of Giving Red Ginger Sour Turmeric Decoction on Menstrual Pain in Adolescent Women. With Mean menstrual pain before being given a decoction of turmeric red ginger acid. Turmeric ginger acid tea is effective in reducing menstrual pain in adolescent girls during menstruation.